Social characteristic of religious rituals - Valentyna Bodak (Українське Pелігієзнавство, 1997)
Society is a person in its social relations. If the term "society" is used to determine reality as a system of interconnections and relationships between people, then its social system appears as an entity in which human societies are diverse in character and social role. Social life is expressed in the grouping of members of society on the basis of certain objectively predetermined types of relations between them. The integrity and unity of religious communities, their qualitative specificity determines the content of the doctrine and cult, on which they grow.